Mahabbah and Muraqabah in Sufism: Strategies for Building the Character of Gen-Z in Indonesia - Anggi Ariska Putri; Chandra Kurniawan; Fadhila Rizqi Maulida; Abid Nurhuda; Dena Sri Anugrah (ESENSI: Jurnal Riset Pendidikan, 2025)
The rapid advancement of information technology has significantly impacted the behavior and character of Generation Z. Amid the rapid digitalization, establishing a strong character based on spiritual values is essential to avoid the negative influences of technology. In this context, two key Islamic conceptsmahabbah (love for Allah) and muraqabah (awareness of Allah's supervision) can serve as effective strategies in shaping the character of Generation Z. This study employs a qualitative literature-based approach to analyze the implementation of these concepts in the daily lives of Generation Z. Data is collected from secondary sources, including books,  academic journals, and relevant articles. The findings reveal that applying mahabah and muraqabah can form an integrated character, enhance self-control, and strengthen morality in the face of technological challenges. Mahabah, as a spiritual foundation, motivates Generation Z to engage in positive behavior, while muraqabah encourages awareness of one's actions and consequences. Therefore, these concepts hold high relevance in character education in the digital age, positioning them as integral and practical strategies for character formation.